This Is Not a Sentence - Paul F. Campos (Washington University Law Quarterly, 1995)
What this symposium on the intersection between linguistic and legal theory illustrates well is that the distinction in legal theory between what is assumed to be a text's inherent formal meaning and its contingent historical meaning essentially replicates the distinction between "sentence meaning" and "utterance meaning" that is crucial to various linguistic theories. The distinction all these theoretical approaches insist on maintaining is that "between the meaning of a sentence and the meaning of an utterance of that sentence on some particular occasion. I think this distinction is illusory and that Georgia Green is correct when she argues that sentences cannot be interpreted out of context, because, as she puts it, "sentences don't occur out of context." Now if this distinction is indeed illusory, then the theoretical project of determining the meaning of a text without reference to the author's intentions is doomed from the start. In fact, it is doomed, because it is oxymoronic. The various intellectual enterprises that depend on the existence of "sentence" or "verbal" meaning (also described as "literal," "conventional," "ordinary," or in traditional legal parlance, "plain" meaning) have been constructed on the basis of a fundamental mistake. The mistake is ontological. "Sentence meaning" simply does not exist in practice-only in theory. Unfortunately (unfortunately, that is, for theories of interpretation), linguistic meaning never exists in theory, only in practice. Textual meaning always occurs in the context of, and indeed is generated by, the intentional semantic content of a particular utterance. Hence you can't have a true theory of linguistic practice any more than you can have a true theory of any other set of contingent facts.
Keywords: Linguistics